Pengaruh Konseling Self Talk terhadap Tingkat Kecemasan - Tambunan, Syafrianto (Madaniyah, 2018)
This study aimed to examine the effect of self-talk to anxiety MTQ participants. This study uses a quasi-experimental approach to design experiments with form Nonequivalent Control Group Design. The subjects were participants MTQ with a total of 12 participants. 6 as an experimental group and 6 participants as the control group. Selection of subjects using quota sampling technique and purposive sampling. Measuring instrument used to measure anxiety is anxiety scale participants adopted from Smith, Smoll, and Schutz (1990). Analysis of data using the Wilcoxon signed rank test by SPSS Statistics ver 2.0. the results showed that the âSelf-Talk influence MTQ example where anxiety participantâ as seen from the Wilcoxon test in pretest and posttest results of the experimental group showed Asymp value. Sig.Â Keywords: Counseling Self Talk, Anxiety, MTQ.